2002
DOI: 10.1002/pds.711
|View full text |Cite
|
Sign up to set email alerts
|

Self‐medication in a Portuguese urban population: a prevalence study

Abstract: In the urban areas under study the overall prevalence of self-medication was 26.2%. Predictive factors for self-medication seem to be, a high level of education, professional status and length of waiting times for a medical consultation in cases of a severe health problem. Further research on this subject is needed to confirm the reproducibility of these results, since potential selection bias could have been introduced due to the method used for patient selection. Pharmacoepidemiologic research is feasible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
93
5
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 4 publications
12
93
5
9
Order By: Relevance
“…These are important factors favouring self-medication and have been reported in other studies [2,10]. Length of waiting time and cost for medical consultation has been identified as one of the triggering factors for self-medication [11]. The most important disadvantages of self-medication are fear of adverse drug reactions and risk of using a wrong drug (fear of the unknown), results similar to those found in an earlier study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These are important factors favouring self-medication and have been reported in other studies [2,10]. Length of waiting time and cost for medical consultation has been identified as one of the triggering factors for self-medication [11]. The most important disadvantages of self-medication are fear of adverse drug reactions and risk of using a wrong drug (fear of the unknown), results similar to those found in an earlier study.…”
Section: Discussionsupporting
confidence: 81%
“…Second year students practice self-medication more often. Previous Studies on self-medication have reported various prevalence figures, ranging from 26.2% [11] to as high as 92% [14]. The commonest illnesses that led to self-medication in this study were usually self-limiting "minor illnesses" that have been widely reported in studies on self-medication as the most common indications [2,10].…”
Section: Discussionmentioning
confidence: 45%
“…Higher levels of education and professional status have been associated with and considered as a predictive factor for self-medication. 13 There is no data on the prevalence and pattern of self-medication in College Students in Delhi (India). Data on the extent of self-medication and reasons for the same may throw light on behavioral patterns related to health seeking among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Entre ellos cabe citar la edad, el sexo, la orientación hacia el autocuidado y el conocimiento de la medicación 7,8,9 .…”
Section: Introductionunclassified